Serine proteases, inhibitors and receptors in renal fibrosis - Eddy, Allison A. (Thrombosis and Haemostasis, 2009)
Chronic kidney disease (CKD) is estimated to affect one in eight adults. Their kidney function progressively deteriorates as inflammatory and fibrotic processes damage nephrons. New therapies to prevent renal functional decline must build on basic research studies that identify critical cellular and molecular mediators. Plasminogen activator inhibitor-1 (PAI-1), a potent fibrosis-promoting glycoprotein, is one promising candidate. Absent from normal kidneys, PAI-1 is frequently expressed in injured kidneys. Studies in genetically engineered mice have demonstrated its potency as a pro-fibrotic molecule. Somewhat surprising, its ability to inhibit serine protease activity does not appear to be its primary pro-fibrotic effect in CKD. Both tissue-type plasminogen activator and plasminogen deficiency significantly reduced renal fibrosis severity after ureteral obstruction, while genetic urokinase (uPA) deficiency had no effect. PAI-1 expression is associated with enhanced recruitment of key cellular effectors of renal fibrosis – interstitial macrophages and myofibroblasts. The ability of PAI-1 to promote cell migration involves interactions with the low-density lipoprotein receptor-associate protein-1 and also complex interactions with uPA bound to its receptor (uPAR) and several leukocyte and matrix integrins that associate with uPAR as co-receptors. uPAR is expressed by several cell types in damaged kidneys, and studies in uPAR-deficient mice have shown that its serves a protective role. uPAR mediates additional anti-fibrotic effects – it interacts with specific co-receptors to degrade PAI-1 and extracellular collagens, and soluble uPAR has leukocyte chemoattractant properties. Molecular pathways activated by serine proteases and their inhibitor, PAI-1, are promising targets for future anti-fibrotic therapeutic agents.
Keywords: Plasminogen activator inhibitor-1; urokinase; fibrosis; urokinase receptor (uPAR)